Analysis of the indications for routine lumbar puncture and results of cerebrospinal fluid examination in children admitted to the paediatric wards of two hospitals in East Africa - Herbert, G; Ndiritu, M; Idro, R; Makani, JB; Kitundu, J (Tanzania Journal of Health Research, 2006)
Lumbar puncture (LP) is an important diagnostic tool for investigating neurological conditions/diseases. This study was carried out to compare the indications for lumbar puncture and findings of cerebrospinal fluid examination in children admitted to Muhimbili National Hospital (MNH) in Dar-es-salaam, Tanzania and Kilifi District Hospital (KDH) in Kenya. Records of all children admitted to the paediatric wards of the two hospitals from 1st November 2004 to 30th April 2005 with suspected central nervous system infections and had LPs performed were analysed. Overall, 8,741 paediatric admissions were recorded in the two hospitals (Muhimbili = 6,228; Kilifi= 2,513). Of these, 607 (6.9%) had a LP performed; 154 out 6,228 (2.5%) in MNH and 453 out of 2,513 (18.0%) in KDH. LPs were performed less frequently in Muhimbili than in Kilifi Hospital. The most common indications for LP at MNH were convulsions (62.5%), neck stiffness (14.3%) and prostration (17%), whereas at KDH were convulsions (56.3%), neck stiffness (7.3%) and prostration (22.1%). The bacterial isolates were rarely (23%) obtained on culture at both hospitals. Streptococcus pneumonaie and Salmonella species were the commonest causes of pyogenic meningitis. In conclusion, the rate of LP performance in the two hospitals is low. There is need therefore to improve the rates of LP and the isolation of bacterial pathogens from cerebrospinal fluid cultures. Other possible causes for meningitis such as viruses need to be investigated. Keywords: lumbar puncture, cerebro-spinal fluid, children, infections, Tanzania, Kenya Tanzania Health Research Bulletin Vol. 8(1) 2006: 7-10